Awareness and Accessibility to Antenatal Health Care Information by Women in Katsina Metropolis - Mashi, Rabiatu Abdulkadir (Communicate: Journal of Library and Information Science, 2022)
Survey research method was adopted to carry out the study. The population of the study was 350 pregnant women attending antenatal care in General hospital Katsina and Turai Umaru Musa Yar’adua Maternal and Child Hospital Katsina. The sample size of the study was the total population because it manageable. Descriptive statistics was used to analyse the data collected. The findings revealed that general health information on pregnancy was the major Antenatal health care information available to women in Katsina metropolis. The study also revealed that women in Katsina metropolis were least aware of information on food hygiene, nutrition and diet and not aware at all about information on medication. The study found that pregnant women in Katsina metropolis access information on antenatal healthcare monthly usually when they visit hospital. Social status and literacy were factors significantly influencing awareness of ANC information while staff delays in attending to patients, long queues and several hours stay at the hospital impede accessibility. The study concluded that pregnant women in Katsina metropolis were not provided with enough Antenatal health care information except for general health education information on pregnancy which was highly available and aware among pregnant women in Katsina metropolis. The study recommended that Katsina state government and other stakeholders should organize trainings, workshops and enlightenment campaigns to create more awareness on the existence of all aspect of ANC information and the importance of utilizing them on regular basis.